CHABOT A Humanoid Robot for Educational and Exhibitional Purposes - Dankis, Karin; Davidsson, Alexander; Hardselius, Erik (My University, 2014)
The CHABOT project entailed the construction of a humanoid robot torso. The robot was to be used in the master program course TIF160 Humanoid Robotics as a laboratory material to be utilized in student group projects. The robot was given the name CHABOT by the customer together with a specified list of functional requirements and a request of an aesthetically pleasing exterior. The main goal of the design was to provide an expandable platform that could be altered with additional functions in the future. This was achieved by using a CAN bus for communication and a combination of 3D printed parts, metal plates and threaded rods creating the supportive skeletal structure. A USB connection between the robot and a computer, allows students to control the entire structure. A polycarbonate plastic shell was crafted to create an engaging and attractive appearance. The final CHABOT prototype fulfilled the stated goals of being both modular, re-creatable and aesthetically pleasing.
Keywords: Grundläggande vetenskaper; Farkostteknik; Hållbar utveckling; Informations- och kommunikationsteknik; Basic Sciences; Vehicle Engineering; Sustainable Development; Information & Communication Technology